1992
DOI: 10.1164/ajrccm/146.5_pt_1.1345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarette Smoking on Rate of Loss of Pulmonary Function in Adults: A Longitudinal Assessment

Abstract: Data from a random sample of 8,191 men and women selected in six U.S. cities and examined on three occasions over a 6-yr follow-up period were analyzed by longitudinal methods to describe the effects of smoking history and current smoking behavior on rate of loss of pulmonary function during adult life. Former smokers had age- and height-adjusted rates of decline (34.3 ml/yr for men and 29.6 ml/yr for women) comparable with those of never smokers (37.8 ml/yr for men and 29.0 ml/yr for women) but much smaller t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
121
2
4

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(157 citation statements)
references
References 1 publication
30
121
2
4
Order By: Relevance
“…As in able-bodied persons, continued smoking was associated with a greater loss of FEV 1 and FVC compared with neversmokers, and the rate of decline was similar to that of ablebodied individuals (26). In our previous cross-sectional analysis, we demonstrated with each pack-year smoked a decrease in FEV 1 of similar magnitude to our current study (4).…”
Section: Discussionsupporting
confidence: 83%
“…As in able-bodied persons, continued smoking was associated with a greater loss of FEV 1 and FVC compared with neversmokers, and the rate of decline was similar to that of ablebodied individuals (26). In our previous cross-sectional analysis, we demonstrated with each pack-year smoked a decrease in FEV 1 of similar magnitude to our current study (4).…”
Section: Discussionsupporting
confidence: 83%
“…From ®ndings by Dockery et al 18 we would project a four percentage-point mean FVC decrement in able-bodied people resembling our 45 years-and-older paraplegics who ever smoked in terms of their mean age, current smoking prevalence, and available pack-year data; whereas our subjects' observed decrement was seven percentage points. Although di erences between current and former smokers were not clear in the present analyses, the earlier separate NY and LA studies, 8,9 as well as numerous studies of able-bodied populations, 10,18,19 attest to long-term lung function bene®ts from stopping smoking.…”
Section: Analyses Including All Levels Of Injurymentioning
confidence: 56%
“…Most studies of smoking e ects in able-bodied populations have focused on airway obstruction (ie, FEV 1 ) rather than FVC, but FVC losses have been observed cross-sectionally 17,18 and longitudinally. 19 Current information, though not de®nitive, is consistent with the possibility that losses are larger in SCI than in able-bodied populations. From ®ndings by Dockery et al 18 we would project a four percentage-point mean FVC decrement in able-bodied people resembling our 45 years-and-older paraplegics who ever smoked in terms of their mean age, current smoking prevalence, and available pack-year data; whereas our subjects' observed decrement was seven percentage points.…”
Section: Analyses Including All Levels Of Injurymentioning
confidence: 87%
“…But, other cross-sectional studies, such as the Beijing respiratory health study [2], a Canadian study [14], the French Cooperative study [8], the Tucson Airways study [15] and both a cross-sectional and longitudinal study from Copenhagen [4,16] have reported a greater decline in lung function among females than males, associated with tobacco smoking. On the other hand, opposite results have been found in both cross-sectional and longitudinal studies, such as the Six Cities study [17], the Tucson Airways Study [18], the cross-sectional part of the Netherlands study [13], the Copenhagen study (after redefining exclusion criteria, but not adjusting for quantity smoked) [19], an Italian study [20] and the UCLA study from Los Angeles [21]. Comparisons between crosssectional and longitudinal studies are distorted, as those with better lung function are more likely to continue in longitudinal studies [13].…”
Section: Tobacco Smoking and Lung Functionmentioning
confidence: 75%